2013
DOI: 10.1111/jzo.12077
|View full text |Cite
|
Sign up to set email alerts
|

Time spent suckling is affected by different social organization in three zebra species

Abstract: Suckling bout duration and frequency were used in the past as an indicator of milk intake. However, later studies found no significant relationship between suckling bout duration and frequency and milk or energy intake. On the other hand recent studies are in line with the suggestion that suckling bout duration and frequency may express intensity of maternal care. The three extant zebra species differ in their ecology and social system. Mountain Equus zebra and Grévy's zebra E. grevyi live in an arid environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…So, instead, we preferred to use the continued focal animal observation method with an even distribution of watching time throughout the day using binoculars (magnification ×8) and a telescope (magnification ×30-×60). We used suckling duration and frequency as main indicators of the degree of maternal investment (Mendl and Paul 1989;Cassinello 2001;Pluhacek et al 2014), even though neither is believed to reflect the actual volume of milk intake (Cameron 1998;Cameron et al 1999). Even so, we believe that these measurements are still useful indicators of the amount of maternal care invested in fawns (Mendl and Paul 1989;Cassinello 2001;Pluhacek et al 2014).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…So, instead, we preferred to use the continued focal animal observation method with an even distribution of watching time throughout the day using binoculars (magnification ×8) and a telescope (magnification ×30-×60). We used suckling duration and frequency as main indicators of the degree of maternal investment (Mendl and Paul 1989;Cassinello 2001;Pluhacek et al 2014), even though neither is believed to reflect the actual volume of milk intake (Cameron 1998;Cameron et al 1999). Even so, we believe that these measurements are still useful indicators of the amount of maternal care invested in fawns (Mendl and Paul 1989;Cassinello 2001;Pluhacek et al 2014).…”
Section: Methodsmentioning
confidence: 98%
“…In these cases, however, it was not made clear why suckles were not recorded and calculated as they were demonstrated naturally by the animal-taking into account all intervals-instead of producing artificial rules for recording this behavior. Fifth, many authors (Shackleton and Haywood 1985;Gauthier and Barrette 1985;Habibi 1987;Lavigueur and Barrette 1992;Cameron et al 1999;Mauget and Mauget 2009;Pluhacek et al 2010Pluhacek et al , 2014 make the assumption that suckles shorter than 5 s are not really suckling, but rather unsuccessful attempts to suckle, while other researchers define different thresholds for nutritive suckles: 3 s for Oryx dammah (Drews 1991) and 8 s for Ovis canadensis (Festa-Bianchet 1988a, b). Certainly, offspring do not typically receive milk at the moment they begin suckling, but a 5-s interval (3 or 8 s in other versions) has not been determined to be a real threshold for milk transfer and is actually an arbitrary cutoff.…”
Section: Introductionmentioning
confidence: 98%
“…African wild ass ( Equus africanus ) and Grevy's zebra ( Equus grevyi ) exhibit resource defence polygyny, with a fission–fusion social system among females (Klingel, ; Rubenstein, ; Sundaresan et al ., ). As the equid species differ in several ethological aspects according to their social organization (Sundaresan et al ., ; Olléová, Pluháček & King, ; Pluháček et al ., ) and overmarking of two related but socially different mammalian species can differ (Kimura, ; Ferkin & Pierce, ), we predicted there would be differences in overmarking between females of harem dwelling and non‐harem dwelling species.…”
Section: Introductionmentioning
confidence: 98%
“…For mothers of various species, lactation may require energy demands that are higher than any other period in the life of the female 4 , 5 . The transfer of milk is an elementary part of reproduction in all mammals, yet species differ considerably with respect to suckling strategies 6 8 . Allosuckling (allonursing), which is the suckling (nursing) of non-filial young 9 , undoubtedly belongs amongst the most interesting suckling strategies 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Other behavioural parameters are frequently used for the expression of maternal care, and they reflect the offspring’s demand rather than the rate of milk transfer 21 23 . These parameters are: suckling bout duration, and/or suckling bout frequency 8 , 24 , 25 . In addition, it was reported that in extreme cases, like allosuckling, these parameters could reflect parent–offspring conflict, as the bout duration may be connected with a shortage of milk, as well as maternal care for filial calves 21 , 22 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%